Risk perception of coronavirus disease 2019 and career adaptability among college students: the mediating effect of hope and sense of mastery - Ding, Yadong; Li, Jing (Frontiers in Psychology, 2023)
The COVID-19 pandemic has not only caused widespread economic recession but also had a serious negative impact on the employment of college students. However, little is known about the relationship and mechanisms between risk perception of COVID-19 and career adaptability. This study aimed to examine whether risk perception of COVID-19 is associated with career adaptability directly and indirectly through hope and the sense of mastery in college students. With a sample of 594 Chinese college students, the results showed that susceptibility was negatively associated with career confidence, control, and curiosity; moreover, susceptibility indirectly affected career adaptability (including concern, confidence, control, and curiosity) through the sense of mastery; uncontrollable indirectly affected career concern through hope; uncontrollability indirectly affected career adaptability (including concern, confidence, control, and curiosity) through hope and sense of mastery.Implications and limitations are discussed.